Diagnoses and nursing interventions contextualized the self-perception of health and individual vulnerabilities in schoolchildren (Research, Society and Development, 2020)
Objective: To identify nursing diagnoses and interventions based on the vulnerability markers of self-perceived negative health in young schoolchildren with overweight. Method: Descriptive study of nursing diagnoses and interventions carried out with 381 young adult students from state schools in Fortaleza-Ceará-Brazil. The study followed all the ethical-legal precepts of studies with human beings, having been approved by the Ethics Committee of the State University of Ceará under protocol number 662,105 / 2014. Results: The nursing diagnoses were: overweight, obesity, self-neglect and risk-prone health behavior. Nursing interventions were promotion of exercise, assistance to reduce weight, nutritional counseling and improvement of coping. Conclusion: There are nursing diagnoses and interventions based on the vulnerability markers of negative self-perceived health, which will subsidize the nurse's care with these young schoolchildren, based on the Nursing Care Systematization.